An efficient polymerase chain reaction approach for the quantitation of multiple RNAs in human tissue samples. - Puntschart, A; Jostarndt, K; Hoppeler, H; Billeter, R (Genome Research, 1994)
We describe a PCR quantitation approach that we have set up to study gene expression in human skeletal muscle biopsies. It is characterized by the independent standardization of the individual steps and ignores attempts to control for the efficiency of the PCR. Different RNA extraction/reverse transcription efficiencies are normalized by the addition of an unrelated cRNA. Quantitation is achieved by parallel amplifications of reference samples containing known amounts of PCR products. Precision was achieved by multiple measurements of several samples. Our approach allows for the detection of less than twofold differences (27-88%, depending on the RNA species studied) among samples. A comparison of biopsies from highly trained endurance runners with biopsies from untrained subjects showed that the increased mitochondrial density in the runners' samples is accompanied by a proportional increase in the concentration of the mRNA of cytochrome c oxidase subunit IV.